Prognosis in Malignant Melanoma with Unknown Primary - Atalay, Can; Yılmaz, Kerim Bora; Altınok, Mehmet (Fırat University, 2007)
Objective: Malignant melanoma patients with unknown primary are encountered rarely and since the number of patients are small, data on their clinical course and prognosis are limited. In this study, malignant melanoma patients with unknown primary are reviewed. Materials and Methods: Malignant melanoma patients with unknown primary were evaluated with respect to age, gender, site of metastases, surgical treatment, adjuvant chemo- / immunotherapy and radiotherapy. Patients' loco-regional recurrences, distant metastases and date of death were recorded to calculate the disease-free and overall survival. Results: Ten patients treated between 1999-2001 were included in the study. Regional lymph nodes were the metastatic sites in all patients and lymph node dissection was performed in all patients. During follow-up, six patients died due to distant metastases in three years (6-34 months) and four patients are alive after four years (48-62 months) without any evidence of disease. Conclusion: In order to obtain long term survival in malignant melanoma patients with unknown primary, curative surgery should be performed and adjuvant therapies should be added. ©2007, Firat University, Medical Faculty

Amaç: Primeri bilinmeyen malign melanom olguları nadir olarak görülürler ve bu gruptaki hastaların sayısı az olduğundan klinik seyirleri ve prognozları hakkındaki mevcut bilgiler kısıtlıdır. Çalışmamızda primeri bilinmeyen malign melanomlu hastaları incelemeyi amaçladık. Gereç ve Yöntem: Primeri bilinmeyen malign melanomu olan hastalar yaş, cinsiyet, metastaz yeri, uygulanan cerrahi ve adjuvan kemoterapi / immünoterapi ve radyoterapi açısından değerlendirildi. Hastalarda saptanan lokal / bölgesel nüksler ve uzak organ metastazları ile ölüm tarihleri kaydedilerek hastalıksız ve tüm sağkalım süreleri hesaplandı. Bulgular: 1999-2001 yılları arasında tedavi edilen 10 hasta çalışmaya alındı. Hastaların tümünde metastaz yeri bölgesel lenf bezleriydi ve cerrahi tedavi olarak tamamına bölgesel lenf bezi diseksiyonu uygulandı. Bu tedaviye, adjuvan kemoterapi / immünoterapi ve radyoterapi eklendi. Takip sırasında, ilk üç yıl (6-34 ay) içinde altı hasta uzak metastazlar nedeniyle ölürken dört hasta en az dört yıldır (48-62 ay) hastalıksız olarak yaşamaktadır. Sonuç: Primeri bilinmeyen malign melanomlu hastalarda uzun süreli sağkalım elde etmek için küratif amaçlı cerrahi tedavi uygulanmalı ve adjuvan tedaviler cerrahiye eklenmelidir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Primeri Bilinmeyen Malign Melanomlarda Prognoz